A multi-responsive luminescent sensor based on a Cd(II) coordination polymer with turn-on sensing toward Al3+ and Cr3+ as well as ratiometric response to norfloxacin. (1st October 2022) - Wu, Yi-Bin; Fu, Lianshe; Dong, Gui-Ying
Graphical abstract: A new ternary Cd(II) coordination polymer (CP) was designed and prepared. Cd(II)-CP can be realized by turn on fluorescent sensors to detect Al 3+ /Cr 3+ as well as ratiometric response to norfloxacin, with high sensitivity, selectivity, and recyclability. Abstract: Luminescent coordination polymers (CPs) can be as promising sensors in which an analyte-induced multi-responsive system with classy recyclability is conducive to the detection of plentiful deadly contaminants. A ternary Cd(II) CP, namely, [Cd(L)0.5 (1, 8-NDC)·H2 O]n (1 ) (1, 8-H2 NDC = 1, 8-naphthalenedicarboxylic acid) was constructed from the new flexibility 1, 5-bis(thiabendazol-1-yl)pentane (L) and 1, 8-H2 NDC ligands under hydrothermal conditions. 1 possesses a 1D chain structure. 1 displays excellent pH resistance and luminescent sensing properties. 1 represents the first-ever CP for significant fluorescence "turn-on" detection of Al 3+ and Cr 3+ ions as well as ratiometric response to norfloxacin (NOR), even with the coexistence of other interferents. The luminescent sensing mechanism of 1 toward different analytes was discussed in detail.